The association between platelet transfusions and mortality in patients with critical illness. Issue 6 (1st April 2019) - Ning, Shuoyan; Liu, Yang; Barty, Rebecca; Cook, Richard; Rochwerg, Bram; Iorio, Alfonso; Warkentin, Theodore E.; Heddle, Nancy M.; Arnold, Donald M.
Abstract : BACKGROUND: Platelet (PLT) transfusions are frequently administered in the setting of critical illness but their clinical impacts remain unknown. This study examined the association between PLT transfusions and death in a large intensive care unit (ICU) patient population. STUDY DESIGN AND METHODS: Using a transfusion registry spanning 2008 to 2015, this study assessed effect of in‐ICU PLT transfusions on ICU and in‐hospital mortality using a stratified, time‐dependent Cox proportional hazards model adjusted for illness severity, thrombocytopenia, and other confounders. Patients with known malignancy were excluded. Exposure to PLT transfusions were analyzed dichotomously (ever or never transfused) and continuously (number of transfusions). Medical, general surgery, and cardiac surgery subgroups were analyzed separately. RESULTS: Overall 32, 842 adult patients were admitted to ICU, and 4927 patients received PLT transfusion(s). Crude in‐ICU and in‐hospital mortality were higher for PLT‐transfused patients compared to nontransfused patients (9.2% vs. 6.7% and 12.3% vs. 9.3%, respectively). After confounders were adjusted for, PLT transfusions (ever vs. never) were not associated with increased mortality in ICU (hazard ratio [HR], 0.78; 95% confidence interval [CI], 0.60‐1.02; p = 0.06) or in hospital (HR, 0.89; 95% CI, 0.68‐1.09; p = 0.41). Continuous exposure analysis also showed no association between PLT transfusions and death. PLT transfusions have a protective effect on in‐hospital mortality in the subgroup of general surgery patients (HR, 0.71; 95% CI, 0.51‐0.99; p = 0.04; ever or never analysis). CONCLUSION: Platelet transfusions were not associated with increased risk of death in critically ill patients. Further studies are required to identify subgroups for which PLT transfusions may be beneficial. Abstract : See editorial on page 1891–1893, in this issue